Reinforced PA glass fiber sizing agent for GMT and preparation method and application thereof
By using aminosilane coupling agent, polyvinylpyrrolidone lubricant, anionic water-based polyurethane emulsion, low molecular weight epoxy emulsion and other components in the GMT production process, the reinforced PA glass fiber sizing agent for GMT solves the problem of glass fiber and PA. The problem of poor resin compatibility is achieved and high-quality composite production is achieved.
Patent Information
- Application Number
- CN202311476875.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-11-08
AI Technical Summary
It is difficult to develop a glass fiber wetting agent that can combine well with polyamide (PA) resins in the prior art. Especially in the GMT production process, the compatibility and mechanical properties of glass fibers with PA resins are insufficient.
The reinforced PA glass fiber sizing agent for GMT uses aminosilane coupling agent, polyvinylpyrrolidone lubricant, anionic water-based polyurethane emulsion and low molecular weight epoxy emulsion as the main components. By optimizing the component ratio and process flow, the glass fiber can be improved. The combination of fiber and PA resin and GMT processability.
It achieves a good combination of glass fiber and PA resin, improves the mechanical properties and processability of composite materials, and meets the needs of GMT production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sizing agents, and in particular relates to a sizing agent for reinforcing PA glass fibers for GMT, and a preparation method and application thereof. Background Art
[0002] Polyamide (PA) has good comprehensive properties, including mechanical properties, wear resistance, heat resistance and self-lubrication, and is easy to process. It is an important engineering plastic. Glass fiber is an important material for reinforcing PA. It mainly has two forms: long glass fiber and short glass fiber. Its reinforcement process is mainly based on twin-screw extrusion and injection molding. GMT is a prepreg of glass fiber thermoplastic. At present, there is little research on glass fiber impregnation agents for GMT to reinforce PA.
[0003] Chinese patent CN 105152550 A discloses a highly versatile alkali-free glass fiber direct yarn sizing agent, the sizing agent is made of coupling agent, lubricant A, lubricant B, film former A, film former B, film former C, surfactant, pH value regulator and deionized water, and the pH value is 3-9: wherein the coupling agent is a silane coupling agent; lubricant A is a cationic lubricant; lubricant B is a non-ionic lubricant; film former A is a non-ionic aqueous polyurethane emulsion; film former B is an aqueous polyester resin emulsion; film former C is an aqueous epoxy resin emulsion; pH value regulator is a mixture of acetic acid, citric acid and boric acid; the solid mass of the sizing agent accounts for 4-10% of the total mass of the sizing agent, and the balance is water. The sizing agent described in this patent uses aqueous polyester resin emulsion and aqueous epoxy resin emulsion as film formers to mainly enhance thermosetting resins such as unsaturated polyester resin and epoxy resin, but has poor binding to PA resin and low mechanical properties.
[0004] Chinese patent CN 112521028 A discloses a glass fiber sizing agent for glass fiber reinforced plastic pipes and a preparation method and device. The sizing agent of the present invention comprises a coupling agent 5-13%, a lubricant A 15-30%, a lubricant B 0.5-3.0%, a film former 49-72%, an antistatic agent 1-8%, and a pH regulator 1-5%. The solid mass of the sizing agent accounts for 3.5-7.5% of the total mass of the sizing agent, and the balance is water. The coupling agent is a reinforced silane coupling agent; the lubricant is a mixture of lubricant A and lubricant B, lubricant A is a polyoxyethylene ether lubricant, and lubricant B is a quaternary ammonium salt lubricant. The film former is a mixture of two different types of epoxy emulsions of film former A and film former B, the antistatic agent is an ammonium salt antistatic agent, and the pH regulator is an organic acid. In this patent, the sizing agent uses bisphenol A type epoxy resin and phenolic modified epoxy resin as film formers to enhance epoxy resin, but has poor compatibility with enhanced PA resin.
[0005] In order to meet the GMT production process and be used to reinforce PA resin, it is necessary to develop a glass fiber sizing agent so that the glass fiber produced has good bonding with PA and meets the GMT production process. Summary of the invention
[0006] The object of the present invention is to provide a PA glass fiber reinforced sizing for GMT, wherein the glass fiber product produced by the sizing has good bonding with PA and meets the GMT production processability; the present invention also provides a preparation method and application of the PA glass fiber reinforced sizing for GMT.
[0007] The PA glass fiber sizing agent for GMT of the present invention is composed of a coupling agent, a lubricant, a film former A, a film former B, an antistatic agent and deionized water, wherein the lubricant is polyvinyl pyrrolidone, the film former A is a polyurethane emulsion, and the film former B is an epoxy emulsion.
[0008] The polyurethane emulsion is an anionic water-based polyurethane emulsion.
[0009] The epoxy emulsion is a low molecular weight epoxy emulsion, and the molecular weight of the low molecular weight epoxy emulsion is 480-580.
[0010] The coupling agent is an aminosilane coupling agent.
[0011] The antistatic agent is a quaternary ammonium salt antistatic agent.
[0012] The solid mass in the impregnating agent accounts for 3-5% of the total mass of the impregnating agent.
[0013] The percentage of the solid mass of each component in the infiltrant to the total solid mass in the infiltrant is as follows:
[0014] Coupling agent 0.1-10%
[0015] Lubricant 1-10%
[0016] Film former A 50-85%
[0017] Film former B 10-40%
[0018] Antistatic agent 0.1-5%.
[0019] The percentage of the solid mass of each component in the infiltrant to the total solid mass in the infiltrant is preferably as follows:
[0020] Coupling agent 0.1-9%
[0021] Lubricant 1-9%
[0022] Film former A 50-80%
[0023] Film former B 10-35%
[0024] Antistatic agent 0.1-4%.
[0025] The percentage of the solid mass of each component in the wetting agent to the total solid mass in the wetting agent is more preferably as follows:
[0026] Coupling agent 0.2-9%
[0027] Lubricant 1-8%
[0028] Film former A 60-75%
[0029] Film former B 12-30%
[0030] Antistatic agent 0.2-3.5%.
[0031] The percentage of the solid mass of each component in the wetting agent to the total solid mass in the wetting agent is more preferably as follows:
[0032] Coupling agent 0.2-8%
[0033] Lubricant 2-7%
[0034] Film former A 62-72%
[0035] Film former B 13-25%
[0036] Antistatic agent 0.2-3%.
[0037] The mass ratio of the film-forming agent A to the film-forming agent B is 1.25-8.5:1, wherein the film-forming agent A is calculated based on the solid mass in the film-forming agent A, and the film-forming agent B is calculated based on the solid mass in the film-forming agent B.
[0038] The method for preparing the PA glass fiber sizing agent for GMT of the present invention comprises the following steps:
[0039] (1) Add coupling agent to deionized water and stir;
[0040] (2) Dilute the lubricant with deionized water, add it and stir;
[0041] (3) Dilute film-forming agent A with deionized water, add and stir;
[0042] (4) Dilute film-forming agent B with deionized water, add it and stir;
[0043] (5) Dilute the antistatic agent with deionized water, add it and stir;
[0044] (6) Add the remaining deionized water to obtain the PA glass fiber impregnation agent for GMT.
[0045] The amount of deionized water added in step (1) is 30-40% of the total mass of the PA glass fiber sizing agent for GMT reinforcement.
[0046] The stirring time in step (1) is 15-20 minutes.
[0047] The mass of the deionized water in step (2) is 3-5 times the mass of the lubricant.
[0048] The mass of the deionized water in step (3) is 2-3 times the mass of the film-forming agent A.
[0049] The mass of the deionized water in step (4) is 2-3 times the mass of the film-forming agent B.
[0050] The mass of the deionized water in step (5) is 2-3 times the mass of the antistatic agent.
[0051] The application of the GMT-reinforced PA glass fiber sizing agent of the present invention is that the GMT-reinforced PA glass fiber sizing agent is used to produce the GMT-reinforced PA glass fiber.
[0052] The aminosilane coupling agent used in the present invention is A-1100, A-1128, A-1387, etc. from Momentive, USA. The coupling agent can link the glass fiber and the matrix resin, and can better improve the bonding between the glass fiber and the resin. The selection of a suitable coupling agent can meet the performance of the enhanced polyamide and meet the GMT production processability.
[0053] The lubricant used in the present invention is polyvinyl pyrrolidone, which can reduce the friction of glass fiber during wire drawing and product processing, and protect the glass fiber from damage during production and subsequent use; the addition of conventional lubricants will affect the combination of glass fiber and resin, but the polyvinyl pyrrolidone lubricant selected in the present invention has good affinity and can be combined with polyamide resin, which is beneficial to enhancing the interface bonding of the composite material.
[0054] In the present invention, film former A is an anionic waterborne polyurethane emulsion, which has excellent compatibility with polyamide resin and ensures the mechanical properties of the composite material. Film former B is a low molecular weight epoxy emulsion with a molecular weight of 480-580. The use of the anionic waterborne polyurethane emulsion in the present invention can provide a good reaction carrier for glass fiber and make the yarn bundle obtain good bundling property; and the use of the low molecular weight epoxy emulsion, on the one hand, introduces epoxy groups into the polyurethane system, so that the composite material has higher strength and toughness, and on the other hand, can reduce the hardness of the yarn bundle and improve the processability. Therefore, the use of anionic waterborne polyurethane emulsion and low molecular weight epoxy emulsion can not only enhance the polyamide resin, but also have GMT processability. The positive charge carried in polyvinyl pyrrolidone has adsorption with the anionic waterborne polyurethane emulsion, and the composite of polyvinyl pyrrolidone and low molecular weight epoxy emulsion can increase the compatibility of low molecular weight epoxy emulsion and emulsion system, and the use of the three in combination increases the stability of the emulsion.
[0055] The antistatic agent in the present invention is a quaternary ammonium salt antistatic agent, and the addition of the antistatic agent improves the dispersion and sedimentation properties of the glass fiber in the GMT process.
[0056] The beneficial effects of the present invention are as follows:
[0057] Compared with the prior art, the use of aminosilane coupling agents in the sizing agent system of the present invention can ensure the interface bonding performance; the use of polyvinyl pyrrolidone lubricant has both lubricity and enhanced bonding with resin; the use of anionic waterborne polyurethane emulsion and low molecular weight epoxy emulsion as film-forming agents can not only enhance the polyamide resin, but also have GMT processability.
[0058] The present invention adopts a suitable and mature glass fiber production process by selecting raw materials and optimizing the proportion of formula components, and the obtained glass fiber is suitable for reinforcing PA resin and meets the GMT production process. The glass fiber yarn bundle produced by the sizing of the present invention has good ribbon properties, does not fall off or knot during use, and has no obvious drawing after short cutting, which meets the GMT production process; the sizing of the present invention is well combined with the PA resin, and the composite material has excellent performance. DETAILED DESCRIPTION
[0059] The present invention is further described below with reference to the embodiments.
[0060] Example 1
[0061] The contents of the components of the sizing agent for reinforcing PA glass fibers for GMT are shown in Table 1. The solid mass in the sizing agent accounts for 3% of the total mass of the sizing agent, and the balance is deionized water.
[0062] The coupling agent is aminosilane coupling agent, and the product brand is Maitu A-1100.
[0063] The lubricant used is Huzhou Shenhua K90.
[0064] Film former A is Baybond® XP 2569 from Bayer.
[0065] The film-forming agent B is low molecular weight epoxy emulsion 296 produced by Taishan Glass Fiber Co., Ltd.
[0066] The antistatic agent used is Kekai 6665.
[0067] The preparation method is as follows:
[0068] (1) Add deionized water to the preparation tank until it accounts for 30% of the total mass of the PA glass fiber sizing agent for GMT reinforcement. Turn on the mixer of the preparation tank, slowly add the coupling agent, and stir for 15 minutes until the solution is clear and transparent without oil spots.
[0069] (2) Dilute the lubricant with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the lubricant.
[0070] (3) Dilute the film-forming agent A with deionized water at room temperature, add it and continue stirring. The mass of deionized water should be twice the mass of the film-forming agent A.
[0071] (4) Dilute the film-forming agent B with deionized water at room temperature, add it and continue stirring. The mass of deionized water should be 3 times the mass of the film-forming agent B.
[0072] (5) Dilute the antistatic agent with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the antistatic agent.
[0073] (6) Add the remaining deionized water to obtain the PA glass fiber impregnation agent for GMT.
[0074] The PA glass fiber sizing agent for GMT was used to prepare the PA glass fiber and composite materials for GMT by conventional methods. The test results of the products are shown in Table 1.
[0075] Example 2
[0076] The contents of the components of the sizing agent for reinforcing PA glass fibers for GMT are shown in Table 1. The solid mass in the sizing agent accounts for 4% of the total mass of the sizing agent, and the balance is deionized water.
[0077] The coupling agent is aminosilane coupling agent, and the product brand is Maitu A-1100.
[0078] The lubricant used is Huzhou Shenhua K90.
[0079] Film former A is Baybond® XP 2569 from Bayer.
[0080] The film-forming agent B is low molecular weight epoxy emulsion 296 produced by Taishan Glass Fiber Co., Ltd.
[0081] The antistatic agent used is Kekai 6665.
[0082] The preparation method is as follows:
[0083] (1) Add deionized water to the preparation tank to 35% of the total mass of the PA glass fiber sizing agent for GMT reinforcement, turn on the mixer of the preparation tank, slowly add the coupling agent, stir for 17 minutes, and stir until the solution is clear and transparent without oil spots;
[0084] (2) Dilute the lubricant with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 4 times the mass of the lubricant.
[0085] (3) Dilute the film-forming agent A with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the film-forming agent A.
[0086] (4) Dilute the film-forming agent B with room temperature deionized water, add it and continue stirring. The mass of deionized water should be twice the mass of the film-forming agent B.
[0087] (5) Dilute the antistatic agent with room temperature deionized water, add it and continue stirring. The mass of deionized water should be twice the mass of the antistatic agent.
[0088] (6) Add the remaining deionized water to obtain the PA glass fiber impregnation agent for GMT.
[0089] The PA glass fiber sizing agent for GMT was used to prepare the PA glass fiber and composite materials for GMT by conventional methods. The test results of the products are shown in Table 1.
[0090] Example 3
[0091] The contents of the components of the sizing agent for reinforcing PA glass fibers for GMT are shown in Table 1. The solid mass in the sizing agent accounts for 5% of the total mass of the sizing agent, and the balance is deionized water.
[0092] The coupling agent is aminosilane coupling agent, and the product brand is Maitu A-1100.
[0093] The lubricant used is Huzhou Shenhua K90.
[0094] Film former A is Baybond® XP 2569 from Bayer.
[0095] The film-forming agent B is low molecular weight epoxy emulsion 296 produced by Taishan Glass Fiber Co., Ltd.
[0096] The antistatic agent used is Kekai 6665.
[0097] The preparation method is as follows:
[0098] (1) Add deionized water to the preparation tank to 40% of the total mass of the PA glass fiber sizing agent for GMT reinforcement, turn on the mixer of the preparation tank, slowly add the coupling agent, stir for 20 minutes, and stir until the solution is clear and transparent without oil spots;
[0099] (2) Dilute the lubricant with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 5 times the mass of the lubricant.
[0100] (3) Dilute the film-forming agent A with deionized water at room temperature, add it and continue stirring. The mass of deionized water should be twice the mass of the film-forming agent A.
[0101] (4) Dilute the film-forming agent B with deionized water at room temperature, add it and continue stirring. The mass of deionized water should be 3 times the mass of the film-forming agent B.
[0102] (5) Dilute the antistatic agent with room temperature deionized water, add it and continue stirring. The mass of deionized water should be twice the mass of the antistatic agent.
[0103] (6) Add the remaining deionized water to obtain the PA glass fiber impregnation agent for GMT.
[0104] The PA glass fiber sizing agent for GMT was used to prepare the PA glass fiber and composite materials for GMT by conventional methods. The test results of the products are shown in Table 1.
[0105] Example 4
[0106] The contents of the components of the sizing agent for reinforcing PA glass fiber for GMT are shown in Table 1. The other contents are the same as those in Example 1. The test results of the product are shown in Table 1.
[0107] Example 5
[0108] The contents of the components of the sizing agent for reinforcing PA glass fiber for GMT are shown in Table 1. The other contents are the same as those in Example 1. The test results of the product are shown in Table 1.
[0109] Comparative Example 1
[0110] The contents of the components of the glass fiber sizing agent are shown in Table 1. The solid mass in the sizing agent accounts for 3% of the total mass of the sizing agent, and the balance is deionized water.
[0111] The coupling agent is aminosilane coupling agent, and the product brand is Maitu A-1100.
[0112] The lubricant used is Huzhou Shenhua K90.
[0113] Film former A is Baybond® XP 2569 from Bayer.
[0114] The antistatic agent used is Kekai 6665.
[0115] The preparation method is as follows:
[0116] (1) Add deionized water to the preparation tank to 30% of the total mass of the glass fiber sizing agent, turn on the mixer of the preparation tank, slowly add the coupling agent, stir for 15 minutes, and stir until the solution is clear and transparent without oil spots;
[0117] (2) Dilute the lubricant with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the lubricant.
[0118] (3) Dilute the film-forming agent A with deionized water at room temperature, add it and continue stirring. The mass of deionized water should be twice the mass of the film-forming agent A.
[0119] (4) Dilute the antistatic agent with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the antistatic agent.
[0120] (5) Add the remaining deionized water to obtain the glass fiber impregnating agent.
[0121] The reinforced PA glass fiber and composite materials for GMT were prepared by conventional methods using glass fiber sizing agents. The test results of the products are shown in Table 1.
[0122] Comparative Example 2
[0123] The contents of the components of the glass fiber sizing agent are shown in Table 1. The solid mass in the sizing agent accounts for 3% of the total mass of the sizing agent, and the balance is deionized water.
[0124] The coupling agent is aminosilane coupling agent, and the product brand is Maitu A-1100.
[0125] The lubricant used is Huzhou Shenhua K90.
[0126] The film-forming agent B is low molecular weight epoxy emulsion 296 produced by Taishan Glass Fiber Co., Ltd.
[0127] The antistatic agent used is Kekai 6665.
[0128] The preparation method is as follows:
[0129] (1) Add deionized water to the preparation tank to 30% of the total mass of the glass fiber sizing agent, turn on the mixer of the preparation tank, slowly add the coupling agent, stir for 15 minutes, and stir until the solution is clear and transparent without oil spots;
[0130] (2) Dilute the lubricant with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the lubricant.
[0131] (3) Dilute the film-forming agent B with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the film-forming agent B.
[0132] (4) Dilute the antistatic agent with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the antistatic agent.
[0133] (5) Add the remaining deionized water to obtain the glass fiber impregnating agent.
[0134] The reinforced PA glass fiber and composite materials for GMT were prepared by conventional methods using glass fiber sizing agents. The test results of the products are shown in Table 1.
[0135] Comparative Example 3
[0136] The contents of the components of the glass fiber sizing agent are shown in Table 1. The solid mass in the sizing agent accounts for 3% of the total mass of the sizing agent, and the balance is deionized water.
[0137] The coupling agent is aminosilane coupling agent, and the product brand is Maitu A-1100.
[0138] The lubricant used is a quaternary ammonium salt lubricant, the brand is Kekai 6760L.
[0139] Film former A is Baybond® XP 2569 from Bayer.
[0140] The film-forming agent B is low molecular weight epoxy emulsion 296 produced by Taishan Glass Fiber Co., Ltd.
[0141] The antistatic agent used is Kekai 6665.
[0142] The preparation method is as follows:
[0143] (1) Add deionized water to the preparation tank to 30% of the total mass of the glass fiber sizing agent, turn on the mixer of the preparation tank, slowly add the coupling agent, stir for 15 minutes, and stir until the solution is clear and transparent without oil spots;
[0144] (2) Dilute the lubricant with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the lubricant.
[0145] (3) Dilute the film-forming agent A with deionized water at room temperature, add it and continue stirring. The mass of deionized water should be twice the mass of the film-forming agent A.
[0146] (4) Dilute the film-forming agent B with deionized water at room temperature, add it and continue stirring. The mass of deionized water should be 3 times the mass of the film-forming agent B.
[0147] (5) Dilute the antistatic agent with room temperature deionized water, add it and continue stirring. The mass of deionized water should be 3 times the mass of the antistatic agent.
[0148] (6) Add the remaining deionized water to obtain the glass fiber impregnating agent.
[0149] The reinforced PA glass fiber and composite materials for GMT were prepared by conventional methods using glass fiber sizing agents. The test results of the products are shown in Table 1.
[0150]
[0151] It can be seen from Table 1 that the yarn bundles of Examples 1-5 have good ribbon-forming properties, are not untied or knotted, and have no obvious drawing when chopped, and the processability is significantly better than that of Comparative Examples 1-3. At the same time, by comparing the performance of the composite materials, the tensile strength, bending strength and impact strength of Examples 1-5 are all better than those of Comparative Examples 1-3. Comparative Examples 2 and 3 have poor bonding with PA resin, and the performance of the composite materials is poor, and the yarn bundle of Comparative Example 3 has large hairy fibers.
Claims
1. A PA glass fiber sizing agent for GMT, characterized in that The invention is composed of a coupling agent, a lubricant, a film-forming agent A, a film-forming agent B, an antistatic agent and deionized water, wherein the lubricant is polyvinyl pyrrolidone, the film-forming agent A is a polyurethane emulsion, and the film-forming agent B is an epoxy emulsion; The polyurethane emulsion is an anionic water-based polyurethane emulsion; The epoxy emulsion is a low molecular weight epoxy emulsion, and the molecular weight of the low molecular weight epoxy emulsion is 480-580; The percentage of the solid mass of each component in the infiltrant to the total solid mass in the infiltrant is as follows: Coupling agent 0.1-10% Lubricant 1-10% Film former A 50-85% Film former B 10-40% Antistatic agent 0.1-5%.
2. The PA glass fiber sizing for GMT according to claim 1, characterized in that The coupling agent is an aminosilane coupling agent.
3. The PA glass fiber sizing agent for GMT according to claim 1, characterized in that The antistatic agent is a quaternary ammonium salt antistatic agent.
4. The PA glass fiber sizing for GMT according to claim 1, characterized in that The solid mass in the impregnating agent accounts for 3-5% of the total mass of the impregnating agent.
5. The PA glass fiber sizing for GMT according to claim 1, characterized in that The mass ratio of the film-forming agent A to the film-forming agent B is 1.25-8.5:1, wherein the film-forming agent A is calculated based on the solid mass in the film-forming agent A, and the film-forming agent B is calculated based on the solid mass in the film-forming agent B.
6. A method for preparing the PA glass fiber sizing for GMT according to any one of claims 1 to 5, characterized in that The steps include: (1) Add coupling agent to deionized water and stir; (2) Dilute the lubricant with deionized water, add it and stir; (3) Dilute film-forming agent A with deionized water, add and stir; (4) Dilute film-forming agent B with deionized water, add it and stir; (5) Dilute the antistatic agent with deionized water, add it and stir; (6) Add the remaining deionized water to obtain the PA glass fiber impregnation agent for GMT.
7. An application of the PA glass fiber sizing for GMT according to any one of claims 1 to 5, characterized in that The PA glass fiber sizing agent for GMT is used to produce PA glass fiber for GMT.
Citation Information
Patent Citations
Impregnating agent for highly-universal alkali-free glass fiber direct roving
CN105152550A
Glass fiber impregnating agent for glass fiber reinforced plastic pipeline and preparation method and device
CN112521028A
Glass fiber impregnating compound for transparent felt as well as preparation method and application of transparent felt
CN108249783A
Glass fiber impregnating agent and application thereof to preparation of alkali free direct yarns for continuous fiber enhanced polyamide
CN108863109A